Co-inoculation of Trichoderma viride with Azospirillum brasilense could suppress the development of Harpophora maydis-infected maize in Egypt - Elmeihy, Rasha M.; Hewedy, Omar A.; Alhumaidi, Maryam S.; Altammar, Khadijah A.; Hassan, Eman O.; El-Debaiky, Samah A. (Frontiers in Plant Science, 2025)
Plant diseases caused by fungal pathogens are responsible for severe damage to strategic crops worldwide. Late wilt disease (LWD) is a vascular disease that occurs late in maize development. Harpophora maydis, the causative agent of maize LWD, is responsible for significant economic losses in Egypt. Therefore, the aim of this study was to control LWD of maize using an alternative approach to reduce the use of chemical pesticides. A combination of Trichoderma viride, a fungal biocontrol agent, and Azospirillum brasilense, a bacterial endophytic plant growth promoter, was applied in vitro and in planta. T. viride showed high mycoparasitic potential against H. maydis via various antagonistic activities, including the production of lytic enzymes, secondary metabolites, volatile compounds, and siderophores. A. brasilense and T. viride filtrates were also shown to suppress H. maydis growth, in addition to their ability to produce gibberellic and indole acetic acids. A significant change in the metabolites secreted by T. viride was observed using GC/MS in the presence of H. maydis. A field experiment was conducted on susceptible and resistant hybrids of maize to evaluate the antagonistic activity of T. viride combined with A. brasilense on LWD incidence as well as plant growth promotion under field conditions. The data revealed a significant decrease in both disease incidence and severity in maize plants treated with T. viride and/or A. brasilense. Further, there was a noticeable increase in all plant growth and yield parameters. An anatomical examination of the control and inoculated maize roots was also reflective of plant responses under biotic stress. Taken together, the obtained results provide successful eco-friendly management strategies against LWD in maize.